Optimasi waktu proyek konstruksi dengan penambahan jam kerja menggunakan metode crashing (Studi kasus : Proyek pembangunan gedung pusat terpadu RSUD Sidoarjo) - Fakhrulloh , Zudan Arif; Triana, Masca Indra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
In implementing construction projects, the benchmark for project success can be seen from short and timely completion times with minimal costs without forgetting the quality of the work. This study aims to identify the optimal time and cost for the project. The research was conducted on the construction of the Sidoarjo Regional Hospital's Integrated Central Building, which has a target completion time of 194 calendar days and is planned to be finished within 28 weeks. Field data revealed a delay of 5.06% between the 7th and 10th weeks, with actual progress reaching 8.80% compared to the planned 13.86%. These delays negatively impacted the quality of work. To address this issue, an acceleration method (crashing) was applied, using the alternative of extended working hours (overtime) with variations of 1 hour, 2 hours, and 3 hours. The research findings indicated that the optimal overtime increase is 3 hours, reducing the project duration from 194 days to 181 days, an acceleration of 13 days. The total project cost was calculated at Rp. 62,632,208,400.99, reflecting a cost reduction of Rp. 159.417.559,01 compared to the normal cost of Rp. 62,791,626,000.00